2011
DOI: 10.1260/1369-4332.14.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Hybrid Test Validation of a MR Damper Controlled Building with Shake Table Tests

Abstract: Real-time hybrid testing (RTHTing) is a relatively new form of experimental testing where only the critical components of the system are physically tested while the rest of the structure is simulated. A RTHT can provide a cost-effective means for testing semiactive controlled civil structures. This paper describes the experimental validation of the RTHT facility at the University of Connecticut through comparison of RTHT results with corresponding shake table responses of a Magneto-Rheological (MR) fluid dampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As shown in, for example, , MR dampers have been successfully used for controlled damping and optimal control of stay cables. Similar numerical and experimental investigations including hybrid testing were conducted in, for example, , for the vibration reduction of buildings equipped with controlled MR dampers. Controlled MR dampers have also been installed in tuned mass dampers in order to make these passive devices adaptive as, for example, proposed in .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in, for example, , MR dampers have been successfully used for controlled damping and optimal control of stay cables. Similar numerical and experimental investigations including hybrid testing were conducted in, for example, , for the vibration reduction of buildings equipped with controlled MR dampers. Controlled MR dampers have also been installed in tuned mass dampers in order to make these passive devices adaptive as, for example, proposed in .…”
Section: Introductionmentioning
confidence: 99%
“…Data exchange between the experimental substructures and the numerical substructures can reduce the required scope of test procedures without affecting test accuracy (Günay et al, 2015; Mosalam et al, 2016). The real-time dynamic substructuring shaking table (RTDSST) test method was applied to investigate aseismic performance of the structure equipped with control devices (Lee et al, 2007; Lin and Christenson, 2011; Mercan and Ricles, 2009). Tu et al (2018) utilized the RTDSST test method on the composite structure, they studied the behavior of a traditional light-frame wood shear walls with post-tensioned rocking cross-laminated timber panels.…”
Section: Introductionmentioning
confidence: 99%
“…Weber et al [11] studied the performance of structure equipped with a semiactive friction pendulum against the seismic loading and determined the optimal friction coefficient of isolation system for minimizing the structure acceleration. Magnetorheological (MR) damper is also another effective semiactive control system considered separately [12,13] or together with the base isolation system for controlling the structural response [14][15][16][17][18]. Ramallo et al [19] demonstrated the effectiveness of adding a MR damper to conventional isolated structures by achieving notable decreases in base drifts compared to passive systems.…”
Section: Introductionmentioning
confidence: 99%